PENGARUH KUALITAS PELAYANAN, HARGA DAN STRATEGI DIGITAL MARKETING TERHADAP MINAT BELI DI UD. SUARNINGSIH - Budiasni, Ni Wayan Novi; Puspa Sari, Ketut Intan (Komunitas Manajemen Kompetitif, 2023)
The purpose of this study was to determine the quality of service, price and digital marketing strategy for buying interest at UD. Suarningsih. The total population of customers, both male and female, who are customers at UD stores. Suarningsih while the sample in this study were 81 customers. Methods of data collection by using the SPSS application version 29.00 for windows. The results of the study show that service quality has a positive effect on purchase intention at UD. Suarningsih with t count > t table (3.430 > 1.991) with a significant level of 0.001 <0.005. Prices have a positive effect on buying interest at UD. Suarningsih with a t count > t table (3.419 > 1.991) with a significant level of 0.001 <0.005. Digital Marketing strategy has a positive effect on buying interest at UD. Suarningsih with t count > table (2, 479 > 1991) with a significant level of 0.007 <0.005.